“This is not easy”: Unveiling the nuances of discrimination experienced by LGBTQ+ teenagers in Heartstopper Season I (2022) - Trisnawati, Ririn Kurnia; Sutikno, Eka Ugi; Agustina, Mia Fitria; Prameswary, Putri Bintang; Mutyas, Sekar Hayuning (Universitas Ahmad Dahlan, 2024)
A majority of LGBTQ+ students experience harassment or assault based on sexual orientation and gender identity. It is as depicted in the Netflix Series entitled Heartstopper released in 2022. While the show centers on the budding romance between Nick and Charlie, it also delves into the experiences of a wider LGBTQ+ friend group. Thus, the aim of this current study is to examine the portrayal of discrimination experienced by LGBTQ+ teenagers in Heartstopper Season 1 and identify its causes, including the characters of color and those identifying as lesbian and gay. The qualitative approach is used using dialogues and pictures as the main data. Besides, gender theory is also employed to analyze the data features LGBTQ+ characters and the discrimination they experience. The result shows that the discrimination comes from both racial background and general people's expectation. Also, the discrimination against gay characters arguably happens due to the rejection of the community, in this case the same-sex school community. Machoism and masculinity may become the main reasons for rejecting, and thus discriminating against gay students as they are seen as weak and thin. By revealing the causes of such discrimination, we hope that the current research may shed light on how to prevent any discrimination against each other, including people with different sexual orientation.